2008
DOI: 10.1007/s10554-008-9403-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left atrial functions by color tissue Doppler imaging in adults with body mass indexes ≥30 kg/m2 versus those <30 kg/m2

Abstract: Evaluation of atrial function has received less attention than that of the ventricle although normal atrial function is required for optimal overall cardiac function. Obesity is associated with increased cardiovascular morbidity and mortality. In this study, we compared left atrial functions in obese adults (body mass index = BMI >or=30 kg/m(2)) with those in non-obese adults (BMI <30 kg/m(2)) by color tissue Doppler parameters. There were 37 adults with BMI >or=30 kg/m(2) (mean age 36 +/- 11 years) and 26 adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…347,348 In most studies, noninvasive ejection indices such as LV fractional shortening and LVEF have been reported for assessment of LV function in obesity. [348][349][350][351][352][353][354] Even in studies in which LV systolic function was lower in obese than in lean patients, LV ejection phase indices usually remained within the normal range or were mildly impaired in the majority of those with depressed values. [347][348][349][350] In contrast, some studies also found supranormal LV systolic function in obese subjects.…”
Section: Endocrine/metabolic Causes Obesity Cardiomyopathymentioning
confidence: 99%
“…347,348 In most studies, noninvasive ejection indices such as LV fractional shortening and LVEF have been reported for assessment of LV function in obesity. [348][349][350][351][352][353][354] Even in studies in which LV systolic function was lower in obese than in lean patients, LV ejection phase indices usually remained within the normal range or were mildly impaired in the majority of those with depressed values. [347][348][349][350] In contrast, some studies also found supranormal LV systolic function in obese subjects.…”
Section: Endocrine/metabolic Causes Obesity Cardiomyopathymentioning
confidence: 99%
“…In the present study, tissue Doppler imaging was used to assess LA peak systolic and late diastolic strain, which represent LA reservoir function and LA booster pump function, respectively (22). At baseline, LA strain was impaired as compared with previously reported values for healthy controls (23,24). LA reservoir function is determined mainly by LV systolic function and LA wall stiffness (25).…”
Section: Discussionmentioning
confidence: 76%
“…LVDD is common in the obese population and is associated with an adverse cardiovascular prognosis, related to changes in cardiac structure and function associated with hemodynamic volume overload (19, 20). Powell et al (21) associated obesity with impaired LV relaxation and elevated LV diastolic filling pressures.…”
Section: Discussionmentioning
confidence: 99%